Galveston Orientation Amnesia Test (GOAT) - Fürbringer e Silva, Silvia Cristina; Sousa, Regina Márcia Cardoso de (Revista da Escola de Enfermagem da USP, 2009)
Closed head injury (CHI) is frequently followed by post-traumatic amnesia (PTA) and is characterized by a transitory state of confusion and disorientation. The PTA duration has been used to quantify the CHI severity and to predict disorders in cognitive functions, as well as to foresee any alteration in the functional capacity of post-trauma victims. The Galveston Orientation Amnesia Test (GOAT) is the first systematized instrument created, and the most broadly applied, to assess PTA. This article presents the GOAT, the conceptual basis for the development of the instrument, and its adaptation and validation to the Brazilian culture. In addition, the article describes the application of the instrument and makes comments on the restrictions of its use. Brazilian research results showed evidences of the GOAT's validity. They also point to the indicators of post-trauma conditions in which the GOAT must be applied, and highlight the difficulties in the application of the instrument.